Experimental Setup with a Compact Vector Network Analyzer, RGB-D Sensor, and Linear Drive Modules for Imitation Modeling of Microwave Personnel Screening System in Motion - Zhuravlev, Andrey; Razevig, Vladimir; Chizh, Margarita; Dong, Ge; Hu, Boxiong (Proceedings International Radar Symposium, 2020)
This paper describes an experimental setup that was built to explore the capabilities of the new microwave personnel screening system, in which synthetic aperture can be formed due to relative motion of the subject in the vicinity of a sparse compact stationary antenna array, whose antennas are distributed predominantly vertically. In such a system, the position of the subject during predominantly horizontal motion is registered by a depth video sensor to enable coherent radar signal processing for a set of instant poses during a single pass. The setup has a depth video sensor that captures a color image and a depth map of a still scene with a mannequin, while the compact vector network analyzer (VNA), which is moved by a two-dimensional scanner, acquires the samples of the radar signal reflected from the same scene at programmable positions. The mannequin is moved by the third linear drive module along a path, creating a number of still scenes, each to be scanned and captured similarly during a single experiment. The data collected from the depth sensor and VNA is stored for the following numerical experiments on joint processing. Preliminary radar images of concealed objects on mannequin are obtained and demonstrated proving that the setup is capable of acquiring required input data. The use cases of the experimental setup are described toward designing a sparse electronically switched antenna array: finding the required number of microwave channels, choosing proper frequency band and bandwidth, deciding on antenna type and its preferable directivity pattern, and others.